A Chiral Reduced‐Dimension Perovskite for an Efficient Flexible Circularly Polarized Light Photodetector. (2nd March 2020) - Wang, Lin; Xue, Yongxiang; Cui, Minghuan; Huang, Yanmin; Xu, Hongyu; Qin, Chaochao; Yang, Jien; Dai, Haitao; Yuan, Mingjian
Abstract: Chiral quasi‐2D perovskite single crystals (SCs) were investigated for their circular polarized light (CPL) detecting capability. Quasi‐2D chiral perovskites, [( R )‐β‐MPA]2 MAPb2 I7 (( R )‐β‐MPA=( R )‐(+)‐β‐methylphenethylamine, MA=methylammonium), have intrinsic chirality and the capability to distinguish different polarization states of CPL photons. Corresponding quasi‐2D SCs CPL photodetector exhibit excellent detection performance. In particular, our device responsivity is almost one order of magnitude higher than the reported 2D perovskite CPL detectors to date. The crystallization dynamics of the film were modulated to facilitate its carrier transport. Parallel oriented perovskite films with a homogeneous energy landscape is crucial to maximize the carrier collection efficiency. The photodetector also exhibits superior mechanical flexibility and durability, representing a promising candidate for sensitive and robust CPL photodetectors. Abstract : Chirale Quasi‐2D‐Perowskite besitzen eine intrinsische Chiralität und können dadurch zirkular polarisiertes Licht (CPL) detektieren. Ein flexibler chiraler Quasi‐2D‐Perowskit‐Dünnfilm‐Photodetektor wird vorgestellt, der eine ausgezeichnete CPL‐Detektionseffizienz und Haltbarkeit aufweist und ein vielversprechender Kandidat für empfindliche und robuste CPL‐Photodetektoren ist.